1-D Mathematical Modeling and CFD Investigation on Supersonic Steam Ejector in MED-TVC. (August 2015) - Hanafi, A.S.; Mostafa, G.M.; Waheed, A.; Fathy, A.
Abstract: Thermo Vapour Compressor TVC is the heart or prime mover of Multi-Effect Desalination MED system, it is also described as a steam ejector. Steam ejector is an economical device that utilizes high pressure steam to compress low pressure steam without any rotating parts or external power sources. The ejector performance is highly dependent on its geometry and operating conditions. The aim of the present work is to design and obtain steam ejector geometry, based on pre-specified operating conditions, and to investigate the flow behavior inside the ejector by using Computational Fluid Dynamics CFD through using "ANSYS FLUENT 14.5" software. In first section of this paper, 1-D mathematical model is carried out to predict the ejector geometry at designed operating conditions. The second part, describes the flow behavior inside the designed model of the ejector by CFD. CFD is a most reliable tool to reveal the phenomenon of the mixing process at different parts of the supersonic turbulent flow ejector and to study the effect of operating conditions on the effective ejector area. Obtaining such effects, using experimental work, is much costly and difficult. Finally, the results show the effect of the operating conditions on the entrainment ratio and the critical back pressure.